Evaluating government programs for enhancing the welfare of the youth towards entrepreneurship - Conchada, Mitzie Irene P. (Animo Repository, 2017)
The Bureau of Labor and Employment Survey data on youth employment reveal that the Filipino youth are predominant in entrepreneurial activities in the country. The youth is defined by the Youth in Nation Building Act of 1994 (RA 8044) as individuals between the age of 15 and 30 years old. Unfortunately, the youth also experience the highest level of unemployment, where 49 percent of the unemployed belong to the age bracket of 15 to 24 years old. To immediately address this problem of youth unemployment, the government encourages the youth to go to into business. Two of the programs of the government, specifically that of Department of Labor and Employment (DOLE), aimed at reducing the number of unemployed as well as addressing the education for employment needs of the youth are the Youth Education-Youth Employability (YE-YE) Project and Youth Entrepreneurship Support (YES) Project. Applying the propensity score matching (PSM) method on the Community-Based Monitoring System (CBMS) data, the study focused on assessing the impact of government programs—such as the YE-YE and YES projects—in improving the welfare of the Filipino youth. Results show that the youth who availed of one or two of the entrepreneurial programs received higher incomes and wages of around three thousand pesos and two thousand pesos per year, respectively. Despite this favorable results, however, only a small proportion of the youth avail of government-sponsored training and education programs. Hence, there is a need to promote the entrepreneurial programs among the youth and to monitor their progress and continually support their efforts in sustaining entrepreneurial endeavors. © 2017 by De La Salle University.